The Necessary Modification of the Regional Development Methods Regarding to Climate Change Along the Nile River - Somaya Aboelnaga (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
Climate change adds extra stress on the current global situations and the regional development plans. Despite, Africa being rated the least among the continents contributing to the atmospheric pollution, it continues to be responsible for the least global emissions (estimated at 4%). Although they contributed to anthropogenic emission slightly, African continent is one of the highly vulnerable to impacts of long-term climate variability and extreme weather events, especially on the Nile. Moreover, developing countries are the most vulnerable to climate change impacts because they have fewer resources to adapt: socially, technologically and financially. Therefore, this paper is seeking to find and modify the regional development process in the frame of climate change along the Nile river. By considering some examples to accelerate the development process and methods in the Nile’s valley regions. Strongly related to the climate change impacts on different sectors and activities such agriculture, industry, energy, and the water supply and demand as well.